2021
DOI: 10.1007/s00122-021-03997-7
|View full text |Cite
|
Sign up to set email alerts
|

The performance of phenomic selection depends on the genetic architecture of the target trait

Abstract: Key message The phenomic predictive ability depends on the genetic architecture of the target trait, being high for complex traits and low for traits with major QTL. Abstract Genomic selection is a powerful tool to assist breeding of complex traits, but a limitation is the costs required for genotyping. Recently, phenomic selection has been suggested, which uses spectral data instead of molecular markers as predictors. It was shown to be competitive with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This genomic structure impact on genomic prediction models was also reported previously (Riedelsheimer et al 2013;Schopp et al 2017;Werner et al 2020). The absence of impact of genomic structure on PP is in accordance with Zhu et al (2021Zhu et al ( , 2022 and Weiß et al (2022) studies. Therefore, HBLUP models should be preferred to predict complex traits for genetically diverse germplasm.…”
Section: Genomic and Phenomic Predictions Allowed Capturing Weak Poly...supporting
confidence: 91%
See 1 more Smart Citation
“…This genomic structure impact on genomic prediction models was also reported previously (Riedelsheimer et al 2013;Schopp et al 2017;Werner et al 2020). The absence of impact of genomic structure on PP is in accordance with Zhu et al (2021Zhu et al ( , 2022 and Weiß et al (2022) studies. Therefore, HBLUP models should be preferred to predict complex traits for genetically diverse germplasm.…”
Section: Genomic and Phenomic Predictions Allowed Capturing Weak Poly...supporting
confidence: 91%
“…Brault et al (2022) also reported a low correlation between NIRS-based H matrix and SNP-based K matrix using a diversity panel of grapevine. A single study for triticale revealed a H matrix well correlated to the genomic (Zhu et al 2022). The low correlations between H and K matrices, might result from different histories of domestication and selection or from different range of considered genetic diversity.…”
Section: Alleles Promoting Seed Germination Are Almost All Fixed In O...mentioning
confidence: 99%
“…It is also important to note that hybrids used in G2F contains the high genetic diversity, it is likely to expect the high prediction accuracies that does not necessarily reflect a public or special breeding populations ( Windhausen et al 2012 ), but G2F hybrid population is still useful population to compare temporal phenomic and GPs. Successful phenomic prediction studies reported to date have used NIRS data; some of phenomic prediction results performed favorably in comparisons with GP ( Rincent et al 2018 ; Lane et al 2020 ; Lane and Murray 2021 ; Zhu et al 2021 ; Robert et al 2022 ; Weiß et al 2022 ; Zhu et al 2022 ). Drone image-derived data have also been used as complementary data in GP that increased prediction accuracy of grain yield in wheat ( Rutkoski et al 2016 ; Sun et al 2019 ; Galán et al 2020 ; Krause et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages include low cost and robustness across different environments ( Rincent et al, 2018 ). The phenomic selection performed more accurately for complex traits such as grain yield than traits controlled by a few genes ( Zhu et al, 2022 ). Since drought and heat tolerance are considered complex traits, peanut breeders are expected to benefit from phenomic selection and reduce the labor and time required for screening diverse populations.…”
Section: High-throughput Phenomics To Accelerate Data Collection In G...mentioning
confidence: 99%